Evaluation of the Educational System in the Applied Linguistics School: Teaching of English in the Pontifical Catholic University of Ecuador in Esmeraldas - Guerrero Rodriguez, Solange (2014)
Guerrero Rodriguez, Solange: Evaluation of the Educational System in the Applied Linguistics School: Teaching of English in the Pontifical Catholic University of Ecuador in Esmeraldas ; 71 p. ; Tesis previa obtención del título de Licenciad en Lingüística Aplicada mención Enseñanza en Inglés. 2014